1994
DOI: 10.1111/j.1574-6941.1994.tb00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant DNA transfer to Escherichia coli of human faecal origin in vitro and in digestive tract of gnotobiotic mice

Abstract: The role of helper elements in the mobilisation of pBR recombinant plasmids (tra−, mob−, oriT+ and tra−, mob−, oriT−) from genetically engineered Escherichia coli K12 strains to other K12‐strains and to wild‐type E. coli strains of human faecal origin was examined. Transfer experiments were done in the digestive tract of axenic (germ free) and gnotobiotic mice, associated with human faecal flora, HFF. The kinetics of implantation of donors, recipients and transconjugants were determined. Mobilisation of oriT+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…Another hypothesis is that E. coli strains (donor and helper) are eliminated too rapidly in the HFF (faster than the transit marker); but despite this rapid transit, the transfer of the helper plasmid pRK2013 was observed. Other studies have demonstrated the same phenomenon [14,18].…”
Section: Isupporting
confidence: 57%
See 1 more Smart Citation
“…Another hypothesis is that E. coli strains (donor and helper) are eliminated too rapidly in the HFF (faster than the transit marker); but despite this rapid transit, the transfer of the helper plasmid pRK2013 was observed. Other studies have demonstrated the same phenomenon [14,18].…”
Section: Isupporting
confidence: 57%
“…E. coli HB101 carried a helper plasmid pRK2013 [17] that promotes mobilisation of pRRI207 [16]. Recipient strains were E. coli PG1 [18] of human origin, B. uniformis 1004 [16], B. vulgatus and Bacteroides spp. contained in HFF mice (this study).…”
Section: Bacterial Strains Plasmids and Growth Conditionsmentioning
confidence: 99%
“…When plasmid transfer occurs in the digestive tract, the resulting transconjugants are generally unable to become established in that indigenous bacterial community (Duval-Iflah et al, 1994). By contrast, the spreading of plasmids which encode resistance to clinically important antibiotics in pathogenic bacteria has been observed often during antimicrobial therapy, which is believed to modify the normal microbiota and to lower host resistance against colonization by pathogenic plasmid-bearing bacteria (Barza et al, 1987).…”
mentioning
confidence: 99%
“…Indeed, recent work has shown that conjugation in biofilms occurs far more frequently than previously thought [35]. In addition, numerous studies document the transfer of conjugative or mobilisable plasmids in the gut of rats or mice, both in gnotobiotic animals and in animals associated with human gut microflora [19,32].…”
Section: Bacterial Transformationmentioning
confidence: 96%